Beta‐amyloid‐associated episodic memory variation correlates with subicular volume in non‐demented old aged individuals: Neuroimaging / Optimal neuroimaging measures for early detection. (7th December 2020) - Kagerer, Sonja M; Schroeder, Clemens; Van Bergen, Jiri M. G.; Schreiner, Simon J.; Meyer, Rafael; Steininger, Stephanie C.; Laetitia, Vionnet; Gietl, Anton F.; Treyer, Valerie; Buck, Alfred; Pruessmann, Klaas P.; Hock, Christoph; et al.
Abstract: Background: The aggregation of cortical Amyloid β (Aβ) is a hallmark of Alzheimer's Disease (AD). Aβ accumulates during the preclinical stage and characterizes old aged adults at increased risk for AD. Also, low episodic memory (EM) performance within the normal range is linked to an increased risk for AD. This study is aimed at identifying hippocampal subfield atrophy associated with increased risk for AD, as reflected by cortical Aβ burden, and low EM. Method: 69 non‐demented old aged adults were administered 11C‐PiB‐PET and 18F‐Flutemetamol‐PET for measuring Aβ. Ultra high‐field 7 Tesla MRI (TR/TE = 4.8 ms/2.1 ms, 0.6mm 3 ) was used for assessment of hippocampal subfields volumes. Subjects were dichotomized in high versus low levels of cortical Aβ and high versus low EM, as measured by the Verbal Learning and Memory Test (VLMT). Result: Multiple analysis of Variance (MANOVA) showed significant differences in hippocampal subfield volumes. Most distinguished effects on variation of volumes resulted for coexistent criteria "high‐ Aβ" and "low EM" (λ=0.34, p =0.039). Strongest effects resulted for subiculum and molecular layer (F(1, 59)= 16.8, p = 0.002). The interaction between cortical Aβ and episodic memory performance was significant for subiculum only (F(1, 57) = 5.90, p = 0.018). Conclusion: Our data indicate an association between low subicular volume and increased risk for AD in nondemented old aged persons. While our data is consistent with earlier data on subicular atrophy in preclinical AD, it also highlights promise of multivariate analysis for identifying biological risk phenotypes associated with sporadic AD.